1973
DOI: 10.1111/j.1469-8749.1973.tb04861.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Sydenham's Chorea with Haloperidol

Abstract: SUMMARY Four adolescents with a syndrome consistent with Sydenham's chorea were treated with haloperidol, a neuroleptic agent of the butyrophenone series. Haloperidol was given in daily dosages ranging between 1 and 3mg and the abnormal movements in all four patients rapidly disappeared. There were no recurrences of abnormal movements during the course of treatment, but chorea reappeared in one patient when the drug was discontinued after a two‐month course. This quickly resolved when treatment was resumed. Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…For example, reports varied on whether they provided the time to improvement of symptoms (10 out of 44),19,25,27,30,3538,42,55 the time to full remission of symptoms (two out of 44),21,28 or both (13 out of 44) 20,2224,26,32,33,35,41,44–46,52,53. Nine out of 38 studies reviewed improvement in a chorea score at fixed weekly, monthly, or yearly intervals, rather than reporting the time to an observed improvement or recovery 29,40,4751,54,56.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, reports varied on whether they provided the time to improvement of symptoms (10 out of 44),19,25,27,30,3538,42,55 the time to full remission of symptoms (two out of 44),21,28 or both (13 out of 44) 20,2224,26,32,33,35,41,44–46,52,53. Nine out of 38 studies reviewed improvement in a chorea score at fixed weekly, monthly, or yearly intervals, rather than reporting the time to an observed improvement or recovery 29,40,4751,54,56.…”
Section: Resultsmentioning
confidence: 99%
“…However, this literature review identified significant diversity of antibiotic treatment and/or reporting. Twenty-one studies failed to comment on whether primary or secondary penicillin treatment was utilized1921,23,25,26,29,31,3336,39,45,46,48,51,5456 and 10 reports did not comment on the length of treatment or method of delivery 22,24,28,35,40,42–44,51,53. One study reported primary but not secondary penicillin treatment 47.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dopamine receptor antagonists include haloperidol, pimozide and risperidone. Haloperidol is an effective symptomatic medication but it must be titrated slowly to reach maximum effect with minimal toxic manifestations [Shenker et al 1973]. Table 1 summarizes the larger cases series which have addressed the efficacy and safety of treatment options for SC.…”
Section: Symptomatic Treatmentmentioning
confidence: 99%